Single Nucleotide Polymorphism Typing of Mycobacterium ulcerans Reveals Focal Transmission of Buruli Ulcer in a Highly Endemic Region of Ghana - Röltgen, Katharina (Public Library of Science, 2010)
Buruli ulcer (BU) is an emerging necrotizing disease of the skin and subcutaneous tissue caused by Mycobacterium ulcerans. While proximity to stagnant or slow flowing water bodies is a risk factor for acquiring BU, the epidemiology and mode of M. ulcerans transmission is poorly understood. Here we have used high-throughput DNA sequencing and comparisons of the genomes of seven M. ulcerans isolates that appeared monomorphic by existing typing methods. We identified a limited number of single nucleotide polymorphisms (SNPs) and developed a real-time PCR SNP typing method based on these differences. We then investigated clinical isolates of M. ulcerans on which we had detailed information concerning patient location and time of diagnosis. Within the Densu river basin of Ghana we observed dominance of one clonal complex and local clustering of some of the variants belonging to this complex. These results reveal focal transmission and demonstrate, that micro-epidemiological analyses by SNP typing has great potential to help us understand how M. ulcerans is transmitted.